Investigation of the Relationship between the SO2 Production of Different Yeast Strains and Thiamine Concentration - Pühra (Boróczki), B.; Kállay, M.; Korány, K. (International Journal of Horticultural Science, 2001)
Our general conclusion was that the thiamine amounts of 0,6 and 3,0 mg/1 added prior to wine fermentation, resulted in higher free-S02 level in comparison to the control. Furthermore, among the yeast strains examined in our experiments, Uvaferm BC strain produced the highest free-S02 content under the conditions mentioned before. As regards the dynamics of reductone and SO, production, the concentration of the previous one was practically identical in the middle and at the end of the fermentation while the SO2 content — both free- and total — was lower at the end. Thiamine addition did not cause any difference in the organoleptic properties of wines as proved by sensory analysis.